2011
DOI: 10.1007/s11661-011-0801-1
|View full text |Cite
|
Sign up to set email alerts
|

Welding-Induced Microstructure Evolution of a Cu-Bearing High-Strength Blast-Resistant Steel

Abstract: A new high strength, high toughness steel containing Cu for precipitation strengthening was recently developed for naval, blast-resistant structural applications. This steel, known as BlastAlloy160 (BA-160), is of nominal composition Fe-0.05C-3.65Cu-6.5Ni-1.84Cr-0.6Mo-0.1V (wt pct). The evident solidification substructure of an autogenous gas tungsten arc (GTA) weld suggested fcc austenite as the primary solidification phase. The heat-affected zone (HAZ) hardness ranged from a minimum of 353 HV in the coarse-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…The SSGBs were observed to connect via an epitaxial link with the prior austenite grain boundaries of the PMZ, consistent with observations from autogenous weld microstructures. [3] Overall, the microstructure suggested that good wetting and penetration of liquid occurred along the prior austenite grain boundaries.…”
Section: B Hot Ductility Microstructuresmentioning
confidence: 93%
See 2 more Smart Citations
“…The SSGBs were observed to connect via an epitaxial link with the prior austenite grain boundaries of the PMZ, consistent with observations from autogenous weld microstructures. [3] Overall, the microstructure suggested that good wetting and penetration of liquid occurred along the prior austenite grain boundaries.…”
Section: B Hot Ductility Microstructuresmentioning
confidence: 93%
“…The microstructure evolution during welding has been established from autogenous welding experiments and heat-affected zone (HAZ) simulations. [3] Advanced characterization of simulated HAZ microstructures was completed to understand the observed HAZ hardness profile. [4] Atom-probe tomography (APT) results revealing Cu segregation in the single-pass HAZ regions of BA-160 led to concerns of this alloy being susceptible to HAZ liquation cracking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grain refinement is a way to improve the mechanical properties as well as to avoid segregation of elements during solidification of iron alloys. Therefore, some researchers investigated the heterogeneous nucleation of primary crystals on the surface of non‐metallic inclusions, while the others have tried to apply the heterogeneous nucleation theory to practical operations such as welding and casting . The catalytic potential of various inclusions for the heterogeneous nucleation of primary delta ferrite during solidification of steel has been reported for several decades.…”
Section: Introductionmentioning
confidence: 99%
“…The intermetallic compounds exhaust the ductility and increase the risk of brittle fracture of the deformed metal. Bamboo-shaped cracks can also be found in the melting zones (Ref [13][14][15][16]. They have a negative impact on formability during the next materials processing such as rolling and extruding.…”
Section: Introductionmentioning
confidence: 99%